Active Fault Tolerant Control of Networked Control Systems with Random Packet Loss - Li, Lifan; Li, Linjie (Chinese Automation Congress (Online), 2023)
A new fault diagnosis (FD) and fault-tolerant control (FTC) methodology for networked control systems (N CSs) subject to random packet loss is studied. The Bernoulli process is utilized to describe the packet loss. A robust FD observer is constructed to reconstitute the system state and fault. On the basis of the estimated fault information and other measurement data, the model predictive tracking fault-tolerant controller is designed to make the output of the post-fault NCS can still track the given output. The efficacy of the put forward algorithm is authenticated by computer simulation.